2016
DOI: 10.1039/c6nr03181a
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of gold nanoparticles with cysteine in solution: reactive molecular dynamics simulations

Abstract: The dynamics of gold nanoparticle functionalization by means of adsorption of cysteine molecules in water solution is simulated through classical reactive molecular dynamics simulations based on an accurately parametrized force field. The adsorption modes of the molecules are characterized in detail disclosing the nature of the cysteine-gold interactions and the stability of the final material. The simulation results agree satisfactorily with recent experimental and theoretical data and confirm previous findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…We found that the Au 34 –cys P C O H calculated Raman spectrum reproduces with the highest accuracy most of the observed experimental vibrational bands. This result confirms previous findings based on the comparison of experimental data with small models of only four to nine gold atoms and other molecular dynamics results . However, the accuracy of similarity between experimental and calculated Raman spectra for this rotamer in terms of frequencies and amplitudes is improved with the use of our larger cluster model.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the Au 34 –cys P C O H calculated Raman spectrum reproduces with the highest accuracy most of the observed experimental vibrational bands. This result confirms previous findings based on the comparison of experimental data with small models of only four to nine gold atoms and other molecular dynamics results . However, the accuracy of similarity between experimental and calculated Raman spectra for this rotamer in terms of frequencies and amplitudes is improved with the use of our larger cluster model.…”
Section: Resultssupporting
confidence: 91%
“…This result confirms previous findings based on the comparison of experimental data with small models of only four to nine gold atoms [36] and other molecular dynamics results. [73] However, the accuracy of similarity between experimental and calculated Raman spectra for this rotamer in terms of frequencies vibrations. [34,37,71] On the other hand, there are also observable discrepancies: the calculated P C O H spectrum displays two bands at 756 and 813 cm −1 instead of experimental double band corresponding to COO − scissoring at 812 and 832 cm −1 and shows two bands at 641 and 681 cm −1 instead of the experimental triple band corresponding to 662, 682, and 716 cm −1 .…”
Section: Dft-d3 Calculations For Au 34 -Cysteine Systemsmentioning
confidence: 93%
“…Thus, the best performing amino acids (Arg, Lys, His) likely bind to one AuNP with the α‐amino and carboxylate groups while the amino group of the side arm binds to the other (Figure A). This is supported by the fact that the extent of the cluster formed (related to the intensity of the 595 nm‐band) parallels the basicity of each functional group (guanidine > primary amine > imidazole) as evidenced by the p K a of the side arms of each amino acid: 12.5, 10.8, and 6.0 for Arg, Lys, and His, respectively . If this is the correct mode of binding it means that the basicity of the side arms of Arg, Lys, and His correlates with their affinity for the gold surface of the nanoparticles.…”
Section: Discussionmentioning
confidence: 91%
“…However, in the structured heptapeptide the two amino groups at the N‐ and C‐terminus of the sequence have only the option to bind to two different nanoparticles (Figure D). Previously we have reported that thiolated oligopeptides interact with the surface of AuNPs with other functional groups in addition to the thiol the less structured they are. What we observe in the present case is in line with our previous results.…”
Section: Discussionmentioning
confidence: 99%
“…(Federici et al 2001;Smirnov et al 2015;Glaser et al 2006;Pan et al 2016;Ma et al 2017), mainly due to its high melting point, excellent high-temperature mechanical properties, good sputtering resistance, and low deuterium/tritium retention (Yih and Wang 1979;Chen et al 2008;Wang et al 2016;Yang et al 2016). It is well known that the nano-sized materials possess much better electronic, mechanical, and chemical properties than the traditional bulk materials (Mistry et al 2016;Tian et al 2013;Salorinne et al 2016;Gilbert et al 2004;Zhu et al 2016;Monti et al 2016;Guo et al 2015;Su and Buehler 2016;Qi et al 2009;Qi and Lee 2010). In this respect, various nano-sized W samples have been fabricated experimentally by means of such techniques as mechanical alloying and single damascene process flow (Steinh gl et al 2005;Wang et al 2007;Yeong and Thong 2006).…”
Section: Introductionmentioning
confidence: 99%